2004
DOI: 10.1080/02688690400022920
|View full text |Cite
|
Sign up to set email alerts
|

Isolated cervical intramedullary sarcoidosis--a histological surprise

Abstract: We present a case of cervical intramedullary sarcoidosis. A 56 year old woman presented with progressive paraesthesia affecting the lower limbs. MRI revealed an intramedullar lesion from C4-C7. A laminectomy and subtotal resection was carried out for this presumed intramedullary tumour. Pathology revealed this to be a granulomatous lesion with features indicative of sarcoidosis. Postoperatively, there was no change in her neurological function and her symptoms improved with steroid therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 6 publications
0
11
0
3
Order By: Relevance
“…38 -41 Mathieson et al demonstrated that among 31 cases of histologically proven intramedullary sarcoidosis, postoperative deterioration in neurologic function occurred in 50% cases. 42 Thus, several reports suggest that the first surgery should be limited to decompression of the spinal cord and biopsy without complete extirpation in cases of suspected spinal cord sarcoidosis. 10,[43][44][45][46] However, there has been no report describing the effects of spinal cord decompression on lesions in sarcoidosis.…”
Section: Discussionmentioning
confidence: 99%
“…38 -41 Mathieson et al demonstrated that among 31 cases of histologically proven intramedullary sarcoidosis, postoperative deterioration in neurologic function occurred in 50% cases. 42 Thus, several reports suggest that the first surgery should be limited to decompression of the spinal cord and biopsy without complete extirpation in cases of suspected spinal cord sarcoidosis. 10,[43][44][45][46] However, there has been no report describing the effects of spinal cord decompression on lesions in sarcoidosis.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment is implemented to reduce symptoms and can possibly lead to remission. A literature review of histologically proven intramedullary sarcoidosis showed that 50% of patients who underwent a more extensive resection suffered a postoperative deterioration in neurological function [16]. In contrast, the deterioration was only seen in 28% of limited biopsy patients.…”
Section: Discussionmentioning
confidence: 99%
“…In a review of the literature of 48 cases of spinal cord sarcoidosis, intramedullary involvement was seen in 35% of cases, extramedullary involvement in 35% of cases and both were involved in 23% of patients. 3 Half of the cases with intramedullary involvement had evidence of systemic sarcoidosis. The cervical cord was involved in 70% of the cases.…”
Section: Discussionmentioning
confidence: 99%
“…The cervical cord was involved in 70% of the cases. 3 Spinal cord sarcoidosis begins with linear leptomeningeal involvement along the surface of the spinal cord, followed by parenchymal involvement secondary to spread of the inflammatory process along the VirchowRobin perivascular spaces. 4 In the long term there is abatement of the inflammatory process with residual neuronal damage and spinal cord atrophy.…”
Section: Discussionmentioning
confidence: 99%